From challenges to chances in the digital age: psychological transformation in EFL teachers in Chinese teacher education institutions - Deping, Zou; Xiukui, Song (Frontiers in Education, 2025)
IntroductionTraditional teaching methodologies in Chinese teacher education institutions, especially in English as a Foreign Language (EFL) instruction, are undergoing rapid transformation due to digital education initiatives. While the Digital Literacy of Teachers (DLT) framework has been introduced by the Ministry of Education, limited research exists on the psychological adaptation of EFL teachers to digitalization.MethodsThis qualitative study explored the psychological transformation of 18 EFL teachers from six Chinese institutions who participated in a specialized 60-h digital literacy training program. Participants were purposively sampled for diversity, kept teaching reflection diaries, and engaged in in-depth interviews.ResultsPost-training, teachers demonstrated a comprehensive digital mindset, including enhanced digital awareness, technology knowledge and skills, application, professional growth, and social responsibility. This shift not only improved their teaching abilities but also promoted positive psychological adaptation to digital change.DiscussionThe findings underscore the importance of DLT-aligned training programs in supporting EFL teachers’ psychological transformation during digital transitions. Despite the qualitative approach and reliance on self-reported data limiting generalizability, this study illustrates the psychological impacts of digital training and provides practical guidance for implementing the DLT framework. Future research should employ quantitative methods and larger samples to further validate and extend these results.